Mercury in soils of the conterminous United States: patterns and pools - Connor I Olson; Benjamin M Geyman; Colin P Thackray; David P Krabbenhoft; Michael T Tate; Elsie M Sunderland; Charles T Driscoll (Environmental Research Letters, 2022)
Soils account for the largest global mercury reservoirs, but observations are sparse in many regions. The accumulation and turnover of mercury in soils determines whether they act as an atmospheric source or sink. Here, we present a spatial analysis of soil mercury from a large soil survey (three horizons, ∼4800 sites) across the conterminous United States conducted by the U.S. Geological Survey. Soil mercury pools were calculated for 11 layers, cumulatively representing the top 1 m of soil, and totaling 158 ± 2 Gg (±SD) of mercury (20.3 ± 0.2 mg m ^−2 ). Mercury areal density was greatest in mixed forest (27.3 ± 0.5 mg m ^−2 ), cropland (25.3 ± 0.3 mg m ^−2 ), and deciduous forest (25.6 ± 0.5 mg m ^−2 ) ecosystems and lowest in barren (13.5 ± 0.3 mg m ^−2 ) and shrubland (12.6 ± 0.2 mg m ^−2 ) ecosystems. Assessment of the provenance of soil mercury using bedrock titanium normalization suggests that 62%–95% of soil mercury is unexplained by parental sources.